Psychological intervention in disaster situations: A clinical trial and approach guide - Locatelli, Jocelia de Fátima Ribeiro; Fraron, Leonardo Bertuol; Vezaro, Rosani Munaretto; Bonetti, Alisson (Seven Editora, 2024)
This essay presents a model of psychological intervention in disaster situations, highlighting the importance of the work of psychology professionals to promote the emotional well-being and resilience of individuals affected by traumatic events. The document, which addresses assessment, intervention and prevention strategies, based on scientific evidence and ethical practices, aims to help professionals provide effective support at critical moments. Psychologists in disaster interventions must consider not only cultural aspects, but also adhere to the ethical principles and norms of the Regional Council of Psychology (CRP) on secrecy, confidentiality, and storage of documents. Compliance with these guidelines is crucial to ensure responsible professional practices, in accordance with the standards established by the regulatory institution, as specified in Resolution 001/2009, Art. 4. DOI:https://doi.org/10.56238/sevened2023.006-148